Temporizing after Spinal Cord Injury - Volpe, Rebecca L. (The Hastings Center report, 2015)
Mr. C is a twenty-two-year-old who was flown to a level-1 trauma center after diving headfirst into shallow water. Prior to this accident, he was in excellent health. At the scene, he had been conscious but was paralyzed and had no sensation below his neck. The emergency medical services team immobilized Mr. C's neck with a cervical collar and intubated him for airway protection before transport. As Mr. C's medical care proceeds, he expresses a desire for extubation, although it was not clear that he had the capacity to make this (or any other) decision. It also was unclear whether this desire reflected his authentic wishes to be allowed to die or stemmed from feelings of discomfort and agitation. Over a period of several days, Mr. C's sedation was lightened, and the psychiatry service conducted a formal decision-making capacity assessment. Mr. C continues to express a desire to withdraw life-sustaining medical treatment. However, the psychiatry service is concerned that Mr. C seems to lack adequate insight into what it would mean to die. What does it mean to respect Mr. C's autonomy?